Sustav zaštite od gubitaka sinkronizma u prijenosnoj mreži zasnovan na sinkroniziranim mjerenjima : doktorski rad - Ivanković, Igor; Marušić, Ante (Zagreb : I. Ivanković ; Fakultet elektrotehnike i računarstva, 2017)
Zaštita prijenosne mreže za poremećaje kutne nestabilnosti danas se temelji na standardnim uređajima relejne zaštite. Opseg poremećaja kutne stabilnosti kreće se u granicama od malih oscilacija radne snage preko srednjih i velikih oscilacija radne snage, a krajnji oblik je gubitak sinkronizma u prijenosnoj mreži. Postojeći uređaji relejne zaštite imaju određena ograničenja kod zaštite prijenosne mreže za poremećaju gubitka sinkronizma.
U radu se predlaže izrada nove zaštite od gubitka sinkronizma zasnovane na sinkroniziranim mjerenjima. Sinkronizirana mjerenja prikupljaju se centralno za prijenosnu mrežu u sustavu za širi nadzor prijenosne mreže. Ti podaci koji su vremenski sinkronizirani pogodni su za razvoj novih funkcionalnosti zaštite prijenosne mreže koji se ne mogu realizirati s tradicionalnim relejnim zaštitama.
Poremećaj gubitka sinkronizma je specifičan poremećaj te je u tu svrhu razvijen i odgovarajući dinamički matematički model. Taj model je korišten za istraživanje i simuliranje niza scenarija za poremećaj gubitka sinkronizma. Izraditi će se dva modela prijenosne mreže u Matlabu. Osnova za izradu prvog modela je IEEE model s 9 sabirnica. Drugi model je napravljen i razvijen prema hrvatskoj 400 kV mreži, a koji sadrži 6 sabirnica. Oba modela su ispitana i provjerena.
Nova zaštita zasniva se na sinkroniziranim podacima, a koji u ovom slučaju sadrže fazore direktnih komponenti napona i struja. Iz te dvije veličine izvest će se ostale veličine za novu zaštitu. Zaštita sadrži grupu sistemskih zaštitnih funkcija i rezervne funkcije zaštite dalekovoda. Osnovne funkcije zaštite zasnivaju se na kutnim veličinama, koje su dobivene kao razlike kuta napona na krajevima dalekovoda. Osim razlike kuta koriste se i kutna brzina i kutna akceleracija. Nova zaštita ima mogućnost ranog prepoznavanja i određene predikcije tijekom nastanka gubitka sinkronizma. Također sprečava se širenje poremećaja kroz prijenosnu mrežu. Nova zaštita je napravljena u Matlabu i ugrađena je u oba modela prijenosne mreže.
Ključne riječi
zaštita od gubitka sinkronizma, sinkronizirani mjerni podaci, sinkronizirani mjerni uređaj, sustav za širi nadzor prijenosne mreže, matematički dinamički model prijenosne mreže, Matlab, relejna zaštita, zaštita voda
Electrical protection for transmission network in regard of angle instability today is based on standard solution of relay protection devices. Disturbance of angle stability ranges from small oscillations of active power through middle all the way to large scale oscillations, which can develop into out of step conditions in transmission network. Current existing relay protection devices have certain limitations for protecting transmission network during out of step disturbance.
Dissertation proposal is to find and create new protection for out of step conditions based on synchrophasor measurement. For that purpose, synchrophasor measurements were collected in centralized manner on wide area monitoring system in control center. Those data are time synchronized and as such are appropriate for developing new protection functionalities for transmission network, which otherwise cannot be realized using traditional relay protection devices.
Dissertation is organized into seven chapters.

1. Introduction
In this chapter basic facts about why this research work was done will be stated. Transmission system operator control center already had implemented advanced smart grid technology for controlling the transmission system. That was one of the driving force for this research. All substations and power plants connected on high voltage network are completely remotely controlled using advanced information’s and communications technology meaning they would be suitable for implementation of new functionalities for controlling, protecting, metering and other similar processes. Data from almost every Intelligent Electronic Device in substations is exchanged and transferred to control center in real time using communications infrastructure, consequently giving reliable and secure control for transmission network.
Transmission network is a backbone of electric power system in each country and nowadays presents key role player in electricity supply. Transmission system operator needs to maintain his role under pressure of following factors, maximal usage of the existing transmission infrastructure, support for electricity market and connection of every kind of renewable resources.
All type of data from transmission network inflows into control center, synchrophasor data being one of them. These data are one of the most precise of those available to us in the system and new protection and control functions can be created upon this data.
Centralized out of step protection design will be researched in this dissertation utilizing those synchronized data collected in Wide Area Monitoring (WAM) system in control center. Out of step disturbance is specific and very demanding disturbance in transmission network because it is a sort of system disturbance in a way that it is not necessary related to directly one transmission network element, making detection and selective disconnection of elements has some limitations when using standard relay protection devices. Knowledge and experiences collected in operations with WAM system in control center was stepping stone for this work. Early detection and warning for angle instability can be established with newly developed functions, which has better characteristic than the old traditional one. Another major feature is the possibility to prevent the spreading of out of step disturbances through transmission network.
One of the conditions in process of developing idea for new protection function for angle instability (out of step, active power oscillation and small signal stability) was to use only the data which are available in transmission network, meaning the protection doesn’t relies on any measurement from Generation Company (generator).

2. Monitoring, control and protection for disturbance in high voltage transmission system
One example of using smart grid in control center is collecting and processing different type of data through advanced applications. Massive data flow in Supervisory Control And Data Acquisition (SCADA) processed from one control center is presented. Those examples effectively demonstrate how data in control center can be utilized in everyday business processes almost in real time. Well known classification from Fink-Carlsen gives five possible stages for power system operations. Shifting from one stage to another stage in circumstances of angle instability in a matter of seconds out of step condition can develop.
Proposition was made for new classification of layers of protection and control in transmission network. First and third layers already exist in this system. In first layer, we have traditional relay protection and other Intelligent Electronic Devices on lines and transformers. Third layer has several big and complex applications for transmission network control from center. These are SCADA, Energy Management System (EMS), Automation Generation Control (AGC) and Operator Training Simulator (OTS). In second layer a new application should be established. This application will be developed from Wide Area Monitoring (WAM) system, which will be expanded with protections and controls functions. This Wide Area Monitoring Protection And Control (WAMPAC) system will utilize synchrophasor data through which three basic characteristics for each disturbance in transmission network will be defined, range of disturbance, type of disturbance and source or direction of disturbance. Idea is to connect WAMPAC to SCADA system on third layer. In addition, WAMPAC system in general will have two basic sets of protection functions.
Central protection function in WAMPAC system will have angle stability protection for system disturbance in transmission network. It will cover out of step conditions and all range of active power oscillations. Another set of multifunctional line protection includes line back up protection functions, which are very similar or same to traditional line protection in relay. Also some others specific protection functions and monitoring functions will be included in that set.

3. Out of step protection in transmission network
Relay protection devices and functions for out of step conditions that protect generator or line nowadays possess local action possibilities only. They use local measurement and act on local circuit breaker. Generator out of step protection was developed first and afterwards those functionalities were adopted for line protection.
They in general use impedance measurements like a main protection criteria. Determining of all setting parameters in this function requires a detail study work for large portion of transmission network. Setting depends very much of transmission network configuration. Finally, some setting is chosen which covers majority of network configurations. For some cases resetting has to be done. This setting philosophy is hard to implement on several transmission lines in corridor because network configuration dynamically changes over time.
Source for out of step disturbance and active power oscillations disturbance can be created in local network as well as in wider transmission network. Unlike short circuit fault which affects only one element in power system, generator, line or transformer, out of step disturbance can develop anywhere in transmission network with severe far-reaching consequences on some other parts of network. In that case network transmission elements with out of step condition have to be isolated from operation.
Theoretical elaboration for angle instability formations is given in this chapter together with practical examples from transmission network and power plants operations. Motivation for this work was to improve and enhance control of transmission network. It is obvious that some automatic actions have to be proposed for out of step disturbance and this automatic protection functionality is based on synchrophasor measurements.
Bibliografija str. 185-196.